Effect of Ti and TiNb Microalloying on Microstructures and Mechanical Properties of 2200 MPa Low-Alloy Ultra-High-Strength Steels - Wenchao Yu; Ruizhe Jin; Lei Han; Dirong Xie; Ting Sun; Maoqiu Wang; Jie Shi (Metals)
The 2200 MPa low-alloy ultra-high-strength steels microalloyed with Ti (Ti-steel) and Ti and Nb (TiNb-steel) were quenched at 860 °C and tempered at 180 °C, and the mechanical properties, microstructure, and precipitated phase were studied by SEM, TEM, and physicochemical phase analysis. The results of mechanical properties showed that the TiNb-steel had higher strength than the Ti-steel, with a yield strength of 1746 MPa and 1802 MPa and a tensile strength of 2198 MPa and 2232 MPa, respectively. The TiNb-steel had a finer structure than the Ti-steel, with the effective grain sizes being 0.86 μm and 1 μm, respectively. The TiNb-steel had more MC-type carbides than the Ti-steel, and the MC-type carbide contents were 0.24 wt.% and 0.19 wt.%, respectively. The reason for the higher yield strength of the TiNb-steel is that it has higher strengthening effects due to finer grains, a higher density of dislocation, and more precipitation. The reason for the higher tensile strength of the TiNb-steel is that it has a higher coefficient of variable hardening K and a higher strain hardening index n.